Al-Qur’an Sebagai Weltanschauung Revolusi Industri 4.0 Dalam Menghadapi Tantangan Barat Pada Abad Ke-21 - Muhammad Ghifari (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2019)
The phenomenon of revolution industry 4.0 in 21st century influence by values of secularization. In the context related with locality and time wherever discourse about tren revolution industry 4.0 especially in the epistemology as only solution resolve of human problems. While in the aspect transcendent implication in related dimention of divinity (habl minnallah) not procured attention. This Condition happen because western paradigm-secular as important challenge in 21St century is truly influence the idea of revolution industrion 4.0. In other word that the idea is not value free but value laden. This while not refuse that scientist however in west or east influence by paradigm is supply could by religion or culture and others. This Paper offer the function of Qur’an as weltanschauung revolution industry 4.0 in western challenge in 21st century. Where using the philosophy approach placed the Qur’an as scienctist paradigm in onset. This context happen procces of the islamization of science have meaning that implication industry 4.0 related with dimention of divinity (habl Minnallah)The conclusion of paper is created paradigm revolution industry 4.0 section from Islamic science and can attention aspect horizontal as related with humanity (habl minannâsh) and aspect vertical as related with dimention of divinity (habl Minnallah)in concident.